KEDUDUKAN AMICUS CURIAE DALAM INTERVENSI INTERNATIONAL CRIMINAL COURT (ICC) MENANGANI KASUS KEKERASAN SEKSUAL DI AFGHANISTAN - Tajna Putri Jasmine (2024)
The majority of sexual violence cases in Afghanistan do not go through formal judicial procedures, making it necessary for an international court, the International Criminal Court (ICC), to intervene to deal with sexual violence cases in Afghanistan. In its intervention, other interested parties who are not part of the judicial process take part in providing their views on the ongoing case, this is the practice of Amicus Curiae consisting of experts, organizations, or countries. This research aims to analyze the legality of ICC intervention in Afghanistan and Amicus Curiae's role in providing other considerations not stated by the judiciary with its alignment with victims and the international community. The research method used is normative juridical using statutory, conceptual, and case approaches. The results of this study show that as a member state of the Rome Statute, the legalization of the ICC's intervention in Afghanistan is stipulated in Article 17, as well as, the practice of Amicus Curiae in assisting the court can be seen from its role in increasing publicly available information; media to ascertain public views; and helping to ensure the integrity of the application of international law. Therefore, it is necessary to strengthen the role of Amicus Curiae to ensure open access to information to establish legal transparency, and legal considerations in the interests of victims, and implement the judicial process under procedures. Thus, other state parties in dealing with cases of sexual violence can summon Amicus Curiae to help provide legal considerations based on the interests of victims and the international community.